Preparation and Characterization of Tri-channel Hollow Fiber Nanofiltration Membrane - 邓建绵 张亚涛 刘金盾 张浩勤 庞朝辉 (东华大学学报（英文版）, 2011)
Improvement strength is beneficial to the popularization of hollow fiber nanofiltration（NF） membrane.The tri-channel hollow fiber NF membrane was prepared by interfacial polymerization（IP）.The high strength tri-channel hollow fiber ultrafiltration（UF） membrane were used as the support membrane,m-phenylenedianline（m-PDA）,and polyethylenimine（PEI） were used as aqueous phase monomer,and trimesoyl chloride（TMC） was used as organic phase monomer.Fourier transform infrared spectroscopy（FTIR）,scanning electron microscope（SEM）,and gas sorption analyzer（GSA） were applied in structural analysis of NF membrane.Polymer FTIR illustrates the IP occurrence between aqueous phase monomer and organic phase monomer.The SEM images of NF membrane show the formation of a thin dense layer on surface of support membrane after IP.The flux（J） of optimal NF membrane is 11.2 L·m-2· h-1 at the 0.35 MPa operating pressure.Its retention（R） for NaCl,Na2SO4,MgCl2,Xylenol orange,and Neutral red is 17.4%,30.2%,16.1%,94.3%,and 51.0%,respectively.The NF membrane is on negative charge and its pore radius distributes between 0.3-2.0 nm.